Elemental composition of dispersed vitrinite in marine Jurassic source rocks of the Vulcan Sub-basin, Australia: Implications for vitrinite reflectance suppression. (November 2021) - Faiz, M.; Sherwood, N.; Wilkins, R.W.T.
Abstract: The vast majority of petroleum exploration wells in the offshore basins of Western Australia bottom in Jurassic sedimentary rocks for which vitrinite reflectance results commonly appear to be anomalously low. Light element electron probe microanalysis (EPMA) of dispersed vitrinites in five samples of marine, Jurassic, potential source rocks from three petroleum exploration wells drilled in the Vulcan Sub-basin, Timor Sea, enables better understandings of this problem. The elemental abundance of carbon, oxygen, nitrogen, sulphur, aluminium and silicon were measured, and hydrogen content was calculated by difference. The EPMA method was validated by comparison of microprobe results for vitrinite in an Australian, Permian, medium volatile bituminous coal, with those determined by conventional elemental analysis according to the Australian 'standard method'. Results on the Vulcan Sub-basin samples show that hydrogen contents of the Jurassic vitrinites are anomalously high, plotting as 'type II' 'oil prone' organic matter, on a van Krevelen-type diagram (atomic H/C vs O/C), a region normally associated with liptinite macerals. Implications of the EPMA results were investigated using fluorescence alteration of multiple macerals (FAMM) analyses, a laser-based technique that enables determination of the degree of vitrinite reflectance suppression. The elemental analyses, together with associated optical microscopy, confirm the occurrence of vitrinite having suppressed reflectance in marine Jurassic rocks of the Vulcan Sub-basin, which has important consequences for petroleum exploration if using vitrinite reflectance data in modelling thermal maturation and petroleum generation. In addition, the perhydrous vitrinites themselves may have considerably more petroleum generation potential than previously thought. Highlights: First time electron probe has been used to analyse elemental composition of individual vitrinite grains dispersed in rocks. Analyses show that H in vitrinites is higher than for 'normal' vitrinites, for example in Carboniferous & Permian coals. On an H/C-O/C diagram perhydrous vitrinites plot along a pathway associated with liptinites rather than vitrinites. Perhydrous vitrinite in Vulcan Sub-basin have lower reflectance than orthohydrous vitrinite at similar thermal maturity.